Naps in school can enhance the duration of declarative memories learned by adolescents - Lemos, Nathalia; Weissheimer, Janaina; Ribeiro, Sidarta (Frontiers in Systems Neuroscience, 2014)
Sleep helps the consolidation of declarative memories in the laboratory, but the pro-mnemonic effect of daytime naps in schools is yet to be fully characterized. While a few studies indicate that sleep can indeed benefit school learning, it remains unclear how best to use it. Here we set out to evaluate the influence of daytime naps on the duration of declarative memories learned in school by students of 10-15 years old. A total of 584 students from 6th grade were investigated. Students within a regular classroom were exposed to a 15-minute lecture on new declarative contents, absent from the standard curriculum for this age group. The students were then randomly sorted into nap and non-nap groups. Students in the nap group were conducted to a quiet room with mats, received sleep masks and were invited to sleep. At the same time, students in the non-nap group attended regular school classes given by their usual teacher (Experiment I), or English classes given by another experimenter (Experiment II). In Experiment I (n=371), students were pre-tested on lecture-related contents before the lecture, were invited to nap for up to 2 hours, and after 1, 2 or 5 days received surprise tests with similar content but different wording and question order. In Experiment II (n=213), students were invited to nap for up to 50 minutes (duration of a regular class); surprise tests were applied immediately after the lecture, and repeated after 5, 30 or 110 days. Experiment I showed a significant 10% gain in test scores for both nap and non-nap groups 1 day after learning, in comparison with pre-test scores. This gain was sustained in the nap group after 2 and 5 days, but in the non-nap group it decayed completely after 5 days. In Experiment II, the nap group showed significantly higher scores than the non-nap group at all times tested, thus precluding specific conclusions. The results suggest that sleep can be used to enhance the duration of memory contents learned in school.